2009
DOI: 10.1089/jwh.2008.0946
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Participation among Caribbean Hispanic Women Living in New York: Relation to Education, Income, and Age

Abstract: Background: Inadequate participation in physical activity is a serious public health issue in the United States, with significant disparities among population groups. In particular, there is a scarcity of information about physical activity among Caribbean Hispanics, a group on the rise. Methods: Our goal was to accumulate data on physical activity among Caribbean Hispanic women living in New York and determine the relation between physical activity and age, marital status, education, income, primary language,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…It was found that our respondents were having poor overall knowledge (77.4%) about physical exercise which is contradicted to a study done among New York Caribbean Hispanic women (Giardina et al, 2009). However, this finding is concordance to several authors which also found a higher rate of poor knowledge regarding physical exercise (Roos, 2014;Weiler, Feldschreiber, & Stamatakis, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was found that our respondents were having poor overall knowledge (77.4%) about physical exercise which is contradicted to a study done among New York Caribbean Hispanic women (Giardina et al, 2009). However, this finding is concordance to several authors which also found a higher rate of poor knowledge regarding physical exercise (Roos, 2014;Weiler, Feldschreiber, & Stamatakis, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a study reported that the medications used for diabetes, hypertension, and increases in low-density lipoprotein (LDL) have an inverse relationship with vigorous physical exercise (Duncan et al, 2010). (Giardina et al, 2009). Thus it was expected that university academic staffs particularly in medical faculty and those working in clinical setting to have an awareness of the importance of physical exercise as well as possessing an outstanding knowledge regarding the physical exercise in terms of concept, types, intensity and its recommended duration of physical exercise as the medical personnel are considered to be the center of information on health and the frontline of community preventative health services.…”
Section: Introductionmentioning
confidence: 99%
“…105 Among Caribbean Hispanic women in New York, level of education was also strongly correlated with physical activity. 106 The literature on awareness of stroke warning signs and risk factors has methodological limitations. In 1 study, use of closed-ended questions led to higher scores of knowledge than use of open-ended questions.…”
Section: Differences In Disease Awarenessmentioning
confidence: 99%
“…Hispanics are the least physically active ethnic group in the United States 22 and are disproportionately affected by overweight and obesity; 23,24 at each level of body mass index (BMI), Hispanics have a higher prevalence of diabetes than non-Hispanic whites. 23,25,26 This is critical as Hispanics are the largest minority group in the United States, with the highest birth and immigration rates.…”
mentioning
confidence: 99%